Customers’ Perception towards Mobile Number Portability: An Empirical Study: Understanding the Impact of Perception on Customer Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Perception means the sense of perceiving and the word perceive means to become aware of by one of the senses. It is therefore an intelligent observation or understanding. The word perception refers to the intuitive faculty. The word percept is the mental product with the help of this intuitive power the human being including animals perceive or become aware of through the senses or by mind. Other meanings of the word perceive are to discern to apprehend, to understand, to comprehend or to have knowledge. Perception is the process by which we become aware of and give meaning to events around us. It is through our perception that we come to define ‘Reality’. Perceived reality is what individuals experience through one or more of the human senses and the meaning they ascribe to those experiences. Perception is the process by which people organize and obtain meaning from the sensory stimuli they receive from the environment. It is the process by which we make sense of the word. It is not foolproof. No two people in the same situation will perceive it in exactly the same way. Perception has close relation with the personality of the person perceiving the things and culture. To define the personality, the collection of psychological characteristics or traits that determine a person’s preference and the individual style of behavior. Culture is the way in which a society as a whole perceives the world.